Efficacy and safety of traditional Chinese medicine treatment for idiopathic pulmonary fibrosis: An exploratory, randomized, double-blinded and placebo controlled trial - Li, Jiansheng; Yu, Xue-qing; Xie, Yang; Yang, Shu-guang; Zhao, Limin; Zhou, Miao; Meng, Yong (Frontiers in Pharmacology, 2022)
Background and objective: Idiopathic pulmonary fibrosis (IPF) is a critical disease, with limited treatments available. Clinical practices show that traditional Chinese medicine (TCM) has certain efficacy. This study was preliminarily to evaluate the efficacy and safety of TCM treatment based on syndrome differentiation in IPF. Methods: A study design of exploratory, multi-centers, randomized, double-blinded, placebo controlled trial has been adopted. A total of 80 IPF patients from four sub-centers were enrolled. All the patients were randomly assigned into TCM group (TCMG) or control group (CG) in 1:1. Patients in TCMG were given CM granules, as patients in CG given with the placebo of CM granule. All the patients received a 26-week treatment. The efficacy was assessed by acute exacerbations (AEs) of IPF, pulmonary function, clinical symptoms, dyspnea scores (mMRC), health-related quality of life (HRQoL), 6-min walk test (6MWT) and all-cause mortality. Safety has also been assessed. Results: A total of 67 patients completed the trial with 35 in TCM group and 32 in control group. Meaningful differences have been observed in mean changes in AEs (−1.56 times; 95% CI, −2.69 to −0.43, p = 0.01), DLco% (5.29; 95% CI, 0.76 to 9.81, p = 0.02), cough scores (−0.38 points; 95% CI, −0.73 to −0.04, p = 0.03), and 6MWT (30.43 m; 95% CI, 2.85 to 58.00, p = 0.03), with no statistical differences in FEV1, FVC, expectoration, chest tightness, Shortness of breath, Fatigue, Cyanosis, mMRC, CAT, SF-36, and SGRQ total scores in 26 weeks after treatment than before treatment. At of the end of follow-up, a total of 10 patients died, including three and seven in the TCM and control group respectively. And the HR (Hazard ratio) for CM granules in all-cause mortality was 0.39 (95% CI, 0.10–1.52). The drug-related adverse events were not observed. Conclusion: CM granules, as compared with placebo, could reduce frequencies of AEs, improve pulmonary function, HRQoL, exercise capacity and symptoms and signs for IPF to some extent with acceptable side-effect.